Use of Indwelling Urinary Catheters in Nursing Homes: Implications for Quality Improvement Efforts. Issue 11 (19th September 2016) - Gurwitz, Jerry H.; DuBeau, Catherine; Mazor, Kathleen; Sreedhara, Meera; Lemay, Celeste; Spenard, Ann; Pandolfi, Michelle; Johnson, Florence; Field, Terry
Abstract : Objectives: To describe the epidemiology of indwelling urinary catheter use in nursing homes (NHs). Design: Observational cohort study. Setting: A purposeful sampling strategy was used to identify a diverse sample of 28 Connecticut NHs, defined in terms of ownership, quality ratings, and bed size. Participants: Long‐stay (>100 days) residents of study NHs with an indwelling urinary catheter present at any time over a 1‐year period. Measurements: Duration of catheter use was determined, and indications for catheter placement were documented. Indications considered appropriate included urinary retention or outlet obstruction, pressure ulcer (Stage 3 or 4 with risk of contamination by urine), hospice care, and need for accurate measurement of input and output. During quarterly follow‐up assessments, whether the catheter was still in place or had been removed for any reason other than routine maintenance was determined. Results: The overall rate of any urinary catheter use per 100 resident‐beds over a 1‐year period was 4.8 (range 1.0–9.9, median 5.1). Of the 228 residents meeting eligibility criteria, a documented indication for the catheter was present in the NH record for 195 (86%). Of those with a documented indication, 99% (n = 193) had one or more indications deemed appropriate, including urinary retention (83%), pressure ulcer (21%), hospice care (10%), and need for accurate measurement of input and output (6%). The urinary catheter was removed at some point during the period of observation in 49% (n = 111) of participants; those with a shorter duration of catheter use before study enrollment were more likely to have the catheter removed during the follow‐up period. Of the 111 residents who had the catheter removed, 58 (52.3%) had it reinserted at some point during follow‐up. Conclusion: These findings suggest that indwelling urinary catheter use in long‐stay NH residents is uncommon and generally appropriate and that efforts to improve catheter care and outcomes should extend beyond a singular focus on reducing use.